Tolerability, usability and acceptability of dissolving microneedle patch administration in human subjects - Arya, Jaya; Henry, Sebastien; Kalluri, Haripriya; McAllister, Devin V.; Pewin, Winston P.; Prausnitz, Mark R. (Biomaterials, 2017)
To support translation of microneedle patches from pre-clinical development into clinical trials, this study examined the effect of microneedle patch application on local skin reactions, reliability of use and acceptability to patients. Placebo patches containing dissolving microneedles were administered to fifteen human participants. Microneedle patches were well tolerated in the skin with no pain or swelling and only mild erythema localized to the site of patch administration that resolved fully within seven days. Microneedle patches could be administered by hand without the need of an applicator and delivery efficiencies were similar for investigator-administration and self-administration. Microneedle patch administration was not considered painful and the large majority of subjects were somewhat or fully confident that they self-administered patches correctly. Microneedle patches were overwhelmingly preferred over conventional needle and syringe injection. Altogether, these results demonstrate that dissolving microneedle patches were well tolerated, easily usable and strongly accepted by human subjects, which will facilitate further clinical translation of this technology.